A study of the effects of physical dermabrasion combined with chemical peeling in porcine skin. (February 2015) - Kang, Boo Kyoung; Choi, Jeong Hwee; Jeong, Ki Heon; Park, Jong Min; Suh, Dong Hye; Lee, Sang Jun; Shin, Min Kyung
Abstract Background: Many comparative studies of chemical peeling and dermabrasion have been reported. However, rare basic scientific data about the immediate effects after combined treatment with chemical peeling and dermabrasion have been confirmed. Objectives: The aim of this study is to evaluate the effect of the application of physical abrasion in combination with chemical peels. Materials and methods: Three pigs were treated with physical abrasion using a water jet device in combination with an α-hydroxy acid solution, and the skin samples of the control received chemical peeling solution alone. The levels of growth factors and neuropeptides were measured with a multiplex immunoassay. Result: Skin treated with physical dermabrasion combined with chemical peeling showed prominent detachment and swelling of the stratum corneum (SC), and fluid collection in the hair follicles. The mean cell count of CD34 positive fibroblasts and mast cells, levels of epidermal growth factor, fibroblast growth factor-2, vascular endothelial growth factor, and neurotensin, were significantly increased in the tissue treated with physical abrasion combined with a chemical peeling agent, compared to the skin in the control. Conclusion: We concluded that physical dermabrasion combined with chemical peeling can be more effective than chemical peeling alone, for the approach through transfollicular routes.